Corporealities to the limit : The female body as border territory from artistic practice as research - Coca, Diana (apropos [Perspektiven auf die Romania], 2021)
I propose a theoretical-practical approach to the presentation and representation of the female body in artistic creation. That is, the use of the body as a space at the limit, liminal, of danger and transgression, with the consequent potentially re-signifying effects of territory and common space through art. This narration is accompanied by the dissection of the creative process in phases and its final product, where I start from my own body, as testimony, meeting place, object and subject, studying its relationship with the context in an act of defiance to patriarchal authority. In this sense, we could relate it to the de-hierarchisation and proximity to others, in an unregulated but vital encounter of desiring, non-docile subjectivities, which eroticize politics with their irruption into the public sphere, with the intention of living, creating, loving, inventing another society, another perception of the world and other value systems.